2023
DOI: 10.15446/innovar.v33n89.107047
|View full text |Cite
|
Sign up to set email alerts
|

Estilos de liderazgo de los millennials y su influencia en el desempeño de las pequeñas empresas del sector textil manufactura

Ralphi Ricardo Jauregui-Arroyo,
Niria Marleny Goñi Avila,
Evelyn Rondon-Jara

Abstract: Los estilos de liderazgo impactan en el desempeño y la competitividad de las organizaciones; sin embargo, poco se ha estudiado sobre el estilo de liderazgo de los millennials. Por ello, el objetivo de esta investigación fue analizar la influencia de los estilos de liderazgo de los millennials en el desempeño de las pequeñas empresas del sector textil manufactura de Lima Metropolitana. La investigación es cuantitativa, no experimental, transversal y causal. La muestra estuvo conformada por 400 administradores, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…Furthermore, the literature confirms that SMEs are considered as the sector of society that provide economic growth to many countries, generating jobs even if their survival rate over time is too low (Jamali et al, 2015). Similarly, in Peru, it has been reported that small and medium-sized companies contribute to employment opportunities (Barron, 2020;Jauregui-Arroyo et al, 2023) and like most countries, especially developing, it contributes to the reduction of poverty (Wiid et al, 2016). A recent study also pointed out that although medium-sized companies have limited resources and deficient levels of innovation, they are the engine of a country's economy (Ghezzi et al, 2022).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the literature confirms that SMEs are considered as the sector of society that provide economic growth to many countries, generating jobs even if their survival rate over time is too low (Jamali et al, 2015). Similarly, in Peru, it has been reported that small and medium-sized companies contribute to employment opportunities (Barron, 2020;Jauregui-Arroyo et al, 2023) and like most countries, especially developing, it contributes to the reduction of poverty (Wiid et al, 2016). A recent study also pointed out that although medium-sized companies have limited resources and deficient levels of innovation, they are the engine of a country's economy (Ghezzi et al, 2022).…”
Section: Introductionmentioning
confidence: 88%
“…This study was guided by the post positivism paradigm and the quantitative approach (Costin, 2012;Creswell, 2013); this is also an example of causal non-experimental research. The study population consisted predominantly of general managers of medium-sized companies from different age ranges and educational backgrounds similarly to other studies (Jauregui-Arroyo et al, 2023;Kathuria & Porth, 2003;Ramírez-Solis et al, 2022); most of the study participants reported to be the company owners confirming what has been stated in other studies regarding SMEs in Peru (Barron, 2020). Moreover, it has been found that SMEs in Lima-Peru report around 200k to 2.5 million dollars annual profits; and both the secondary sector (manufacturing companies) and tertiary sector (commerce and services companies) report a high presence in Lima (Ministerio de Producción, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…En este sentido, Jauregui et al (2023), mencionan que en cada teoría de liderazgo existen un conjunto de comportamientos, rasgos y patrones que definen el mejor estilo de liderazgo para un usuario en particular.…”
Section: Newstrom (2007)unclassified